2018
DOI: 10.1097/md.0000000000013736
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of acupuncture at pain acupoints for cervical cancer pain

Abstract: This retrospective study aimed to investigate the feasible effectiveness of acupuncture at pain acupoints for the treatment of patients with cervical cancer pain (CCP). A total of 64 cases were analyzed. All these cases were assigned to an acupuncture group or a control group according to the different therapies they received. The cases in the acupuncture group received acupuncture treatment at pain acupoints, while the subjects in the control group underwent acupuncture at regular acupoints. The primary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Generally, the course of cancer is accompanied by chronic pain, which is a serious problem for cancer patients and remarkably affects their quality of life (QOL) [ 7 ]. Therefore, except for the therapies such as surgery, chemotherapy, and radiotherapy to control the proliferation and metastasis of cancer [ 8 , 9 ], pain relief may be beneficial for improving the patient's QOL while also supplementing cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the course of cancer is accompanied by chronic pain, which is a serious problem for cancer patients and remarkably affects their quality of life (QOL) [ 7 ]. Therefore, except for the therapies such as surgery, chemotherapy, and radiotherapy to control the proliferation and metastasis of cancer [ 8 , 9 ], pain relief may be beneficial for improving the patient's QOL while also supplementing cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Pain is a symptom present in advanced stage cancer and its intensity varies according to the location, type of treatment and degree of evolution (Costa & Chaves, 2012). For this study, five articles related to cancer pain were selected and analysed, among which three performed randomised clinical trials, one carried out a pilot study with a retrospective design and one produced an observational study (Bao, Li, et al, 2018; Bao, Seidman, et al, 2018; Bao, Zhi, et al, 2018; Hershman et al, 2018; Kim & Lee, 2018; Meng & Feng, 2018; Ruela et al, 2018). In addition, the population selected for the randomised clinical trials ranged from 27 to 226 participants, while 592 people participated in the observational study (Bao, Li, et al, 2018; Bao, Seidman, et al, 2018; Bao, Zhi, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The study that applied auricular acupuncture (Ruela et al, 2018) selected 31 participants and used ShenMen and Zero Point. While some studies (Kim & Lee, 2018; Meng & Feng, 2018) selected 27 and 64 participants, respectively, for body acupuncture, and used the CV12, ST25, LI4, LR3, PC06, ST36, SP6 acupoints and additionally 0–3 Ashi points. Sessions lasted an average of 30 min, with Kim and Lee (2018) leaving the needles fixed with skin tape (needles measuring .18 × 1.3 × 1.5 mm) for 48–72 h and the patients were instructed to press the needle sites with their hands twice a day.…”
Section: Discussionmentioning
confidence: 99%
“…Estimations based on trial of acupuncture for cervical cancer pain [ 17 ] of 64 patients with changing NRS from baseline of −4.2 in acupuncture group and −2.2 in control group ( P < .01), indicated that a sample of 168 patients (equally divided into control and treatment groups) would suffice to achieve 90% statistical power for detecting a significant greater decrease of NRS in TENS group than in control group at a two-sided significance level of 0.05. For these calculations, patients undergoing TENS were assumed to themselves experience a decrease of 2.2 in pain scores (compared with their baseline pain scores) due to a placebo effect.…”
Section: Methodsmentioning
confidence: 99%